Comparison between Go-GutDx, a novel diagnostic stool test kit with potential impact in low-income countries, and BioFire test. - Quarshie Glover; Xiao Jiang; Alexis Marie Onderak; Abigail Mapes; Fauzia Hollnagel; Joseph Buckley; Chang Hee Kim; Dawd Siraj (PLoS ONE)
Introduction Infectious diarrheal diseases are one of the leading causes of worldwide morbidity and mortality. The incidence of diarrhea is higher in Low-Middle-Income Countries (LMIC), where more than 90% of deaths from diarrheal diseases occur. Diagnostic tests for infectious diarrhea are not readily available in Low-Middle-Income Countries. Our study evaluates a novel, cost-effective, easy-to-use DNA stool testing kit for infectious diarrhea that can easily be rolled out in low-resource settings and has comparable performance to current testing modalities in the USA in terms of diagnostic utility. Methods 435 stool samples were tested using the novel stool testing Kit (Go-GutDx®). The stool samples were in groups of 8 and were tested using floating microspheres DNA extraction followed by Recombinase Polymerase Amplification (RPA) and lateral flow assay detection. Pathogens tested include Clostridium difficile, Campylobacter jejuni, Salmonella enterica Typhimurium, Shigella spp., STEC (stx1, stx2), Vibrio spp., and Yersinia enterocolitica. The same samples were tested using BioFire GI Panel (gold standard), and the results were compared. Descriptive analysis was summarized as raw counts and frequencies and compared using Fisher's exact test. We conducted specificity and sensitivity analysis of the two diagnostic tests using the diagnostic testing package in STATA. Graphical illustrations were conducted using two-way line graphs with custom margins and axis. All analyses with p-values ≤ 0.05 were significant. All analyses were conducted using STATA version 17. Results Results showed a sensitivity of 56.1% for C. difficile, and 58.6% for Campylobacter jejuni. 46.1% for STEC (stx1, stx2), 83.3% for Salmonella, 0% for Yersinia enterocolitica, 66.7% for Vibrio spp and 65.0% for Shigella spp. Specificities were > 97% for all pathogens. The positive predictive value was highest for Campylobacter jejuni 94.4%, followed by C. difficile 93.5%, Salmonella 86.2%, Shigella 76.5%, STEC (stx1, stx2) 50%, Vibrio spp 40%, and Yersinia 0%. The negative predictive value was 75.8% for C. difficile, with all other pathogens being above 98.3%. Table 3. The concordance between BioFire and Go-GutDx® for C. difficile testing was 80%. All other organisms showed a concordance of greater than 97% Table 2. Discussion Our study confirms that Go-GutDx® is a novel diagnostic tool for diarrheal pathogens with statistically comparable sensitivity, specificity, positive and negative predictive values with the current gold standard testing kit, BioFire. In addition, the simplicity of the technology and lower price both to healthcare systems and to patients makes Go-GutDx® an ideal diagnostic test to be implemented in low- and middle-income countries.